Toward a shared leadership environment: insights into retail salespeople's work environment. Issue 2 (3rd April 2022) - van der Berg, Alexandra Martina; Foege, Johann Nils; Nüesch, Stephan
Abstract: The growing digitization puts more pressure on brick-and-mortar businesses in the retail sector by creating new and more complex customer demands that increase the need for cooperative and trustful exchange relationships between supervisors and salespeople. A promising approach to tackle these challenges lies in implementing less hierarchical leadership structures. While sharing leadership on the team level gains traction among practitioners as a viable form of horizontal leadership, research provides little evidence on the conditions and mechanisms that enable a shared leadership work environment for retail salespeople. Especially the role of formal leaders in such a transition remains unclear. To fill this void, we followed a two-study design. We conducted a large-scale survey with 1, 527 salespeople of a German fashion retailer to analyze how formal leadership contributes to the existence of a less hierarchically structured work environment for retail salespeople. Our multiple mediation analysis provides in-depth and context-sensitive insights into conditions and mechanisms that facilitate a shared leadership environment. A subsequent online-based scenario experiment confirms that transformational leadership is a driver for a shared leadership environment. We contribute to the literature by showing that transformational leadership matters not only in business-to-business (B2B) settings but also in traditionally more transactional business-to-consumer (B2C) retail sales settings to create a shared leadership environment.